Tantangan Perkembangan Kognitif Siswa Kelas VI dalam Pembelajaran Deep Learning melalui Project-Based Learning - Nuryuliyanti; Indah Lestari; Mochamad Widjanarko (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Deep learning through Project-Based Learning (PjBL) has become a relevant approach to develop higher-order thinking skills of elementary school students. However, its implementation still faces several challenges, particularly regarding the cognitive development of sixth-grade students. This study aims to analyze the challenges of cognitive development of sixth-grade students in deep learning through Project-Based Learning based on students’ learning experiences and behaviors. This research employed a qualitative approach with a phenomenological study design. The subjects were sixth-grade students and teachers at an elementary school, with data collected through observation, in-depth interviews, and documentation. The results indicate that deep learning through PjBL can enhance students’ critical thinking, problem-solving, and reflective skills. Nevertheless, challenges were identified, including differences in students’ abstract thinking abilities, limited learning independence, difficulties in integrating concepts across subjects, and the need for intensive teacher guidance. These findings suggest that successful implementation of deep learning through PjBL requires careful planning, appropriate scaffolding strategies, and continuous teacher support to optimally foster students’ cognitive development.